Amphibia, Anura, Centrolenidae, Hyalinobatrachium crurifasciatum Myers and Donnelly, 1997: First record from Brazil and geographic distribution map - Rodrigues, Domingos de Jesus; Lima, Marcelo de Morais; Morais, Drausio H. [UNESP]; Kawashita-Ribeiro, Ricardo A. (My University, 2010)
The current note reports the presence of Hyalinobatrachium crurifasciatum at municipality of Cotriguaçu, state of Mato Grosso, Central Brazil. This is the first occurrence of this species in Brazil. © 2010 Check List and Authors.
Keywords: Amphibia; Anura; Centrolenidae; Hyalinobatrachium